Comparative biochemical analysis after steam pretreatment of lignocellulosic agricultural waste biomass from Williams Cavendish banana plant (Triploid Musa AAA group). Issue 11 (November 2015) - Kamdem, Irénée; Jacquet, Nicolas; Tiappi, Florian Mathias; Hiligsmann, Serge; Vanderghem, Caroline; Richel, Aurore; Jacques, Philippe; Thonart, Philippe
The accessibility of fermentable substrates to enzymes is a limiting factor for the efficient bioconversion of agricultural wastes in the context of sustainable development. This paper presents the results of a biochemical analysis performed on six combined morphological parts of Williams Cavendish Lignocellulosic Biomass (WCLB) after steam cracking (SC) and steam explosion (SE) pretreatments. Solid (S) and liquid (L) fractions (Fs) obtained from SC pretreatment performed at 180°C (SLFSC180) and 210°C (SLFSC210) generated, after diluted acid hydrolysis, the highest proportions of neutral sugar (NS) contents, specifically 52.82 ± 3.51 and 49.78 ± 1.39 %w/w WCLB dry matter (DM), respectively. The highest proportions of glucose were found in SFSC210 (53.56 ± 1.33 %w/w DM) and SFSC180 (44.47 ± 0.00 %w/w DM), while the lowest was found in unpretreated WCLB (22.70 ± 0.71 %w/w DM). Total NS content assessed in each LF immediately after SC and SE pretreatments was less than 2 %w/w of the LF DM, thus revealing minor acid autohydrolysis consequently leading to minor NS production during the steam pretreatment. WCLB subjected to SC at 210°C (SC210) generated up to 2.7-fold bioaccessible glucan and xylan. SC and SE pretreatments showed potential for the deconstruction of WCLB (delignification, depolymerization, decrystallization and deacetylation), enhancing its enzymatic hydrolysis. The concentrations of enzymatic inhibitors, such as 2-furfuraldehyde and 5-(hydroxymethyl)furfural from LFSC210, were the highest (41 and 21 µg ml −1, respectively). This study shows that steam pretreatments in general and SC210 in particular are required for efficient bioconversion of WCLB. Yet, biotransformation through biochemical processes (e.g., anaerobic digestion) must be performed to assess the efficiency of these pretreatments.